Associations between bride price stress and intimate partner violence amongst pregnant women in Timor-Leste - Susan Rees; Mohammed Mohsin; Alvin Kuowei Tay; Elisa Soares; Natalino Tam; Zelia da Costa; Wietse Tol; Derrick Silove (BMC, 2017)
Abstract Background Reducing violence against women is a global public health priority, particularly in low-income and conflict-affected societies. However, more needs to be known about the causes of intimate partner violence (IPV) in these settings, including the stress of bride price obligations. Methods The representative study of women attending ante-natal clinics in Dili, Timor-Leste was conducted between June, 2013 and September, 2014 with 1672 pregnant women, a response rate of 96%. We applied contextually developed measures for the stress of bride price and poverty, and the World Health Organisation measure for intimate partner violence. Results Compared to those with no problems with bride price, women with moderate or serious problems with that custom reported higher rates of IPV (18.0% vs. 43.6%). Adjusting for socio-demographic factors, multivariate analysis revealed that ongoing poverty (OR = 1.75, 95% CI: 1.20-2.56) was significantly associated with IPV. Importantly, the strongest association with IPV was problems with bride price (OR = 2.73, 95% CI: 1.86-4.01). Conclusions This is the first large consecutively sampled study to demonstrate a strong association between the stressors of bride price and poverty with IPV. Notably, bride price stress had the strongest association with IPV. Revealing this hitherto unrecognized factor of bride price stress may prove pivotal in guiding policy and interventions aimed at reducing IPV, and thereby improve the health and psychosocial status of women in low income and conflict-affected settings.